(untitled) (Journal of Applied Oral Science, 2013)
Patients with Vitamin D-resistant rickets have abnormal tooth morphology such as thin globular dentin and enlarged pulp horns that extend into the dentino-enamel junction. Invasion of the pulp by microorganisms and toxins is inevitable. The increased fibrotic content of the pulp, together with a reduced number of odontoblasts, decreases the response to pulp infection. The most important oral findings are characterized by spontaneous gingival and dental abscesses occuring without history of trauma or caries. Radiographic examinations revealed large pulp chambers, short roots, poorly defined lamina dura and hypoplastic alveolar ridge. These dental abscesses are common and therefore the extraction and pulpectomy are the treatment of choice. The purpose of this article is to report a case of Vitamin D-resistant rickets in a 5 year-old boy, describing the dental findings and the treatment to be performed in these cases.